Toxin Enzyme Immunoassays Detect Clostridioides difficile Infection With Greater Severity and Higher Recurrence Rates. (7th January 2019) - Guh, Alice Y; Hatfield, Kelly M; Winston, Lisa G; Martin, Brittany; Johnston, Helen; Brousseau, Geoffrey; Farley, Monica M; Wilson, Lucy; Perlmutter, Rebecca; Phipps, Erin C; Dumyati, Ghinwa K; Nelson, Deborah; et al.
Abstract: Background: Few data suggest that Clostridioides difficile infections (CDIs) detected by toxin enzyme immunoassay (EIA) are more severe and have worse outcomes than those detected by nucleic acid amplification tests (NAATs) only. We compared toxin- positive and NAAT-positive-only CDI across geographically diverse sites. Methods: A case was defined as a positive C. difficile test in a person ≥1 year old with no positive tests in the prior 8 weeks. Cases were detected during 2014–2015 by a testing algorithm (specimens initially tested by glutamate dehydrogenase and toxin EIA; if discordant results, specimens were reflexed to NAAT) and classified as toxin positive or NAAT positive only. Medical charts were reviewed. Multivariable logistic regression models were used to compare CDI-related complications, recurrence, and 30-day mortality between the 2 groups. Results: Of 4878 cases, 2160 (44.3%) were toxin positive and 2718 (55.7%) were NAAT positive only. More toxin-positive than NAAT-positive-only cases were aged ≥65 years (48.2% vs 38.0%; P < .0001), had ≥3 unformed stools for ≥1 day (43.9% vs 36.6%; P < .0001), and had white blood cell counts ≥15 000 cells/µL (31.4% vs 21.4%; P < .0001). In multivariable analysis, toxin positivity was associated with recurrence (adjusted odds ratio [aOR], 1.89; 95% confidence interval [CI], 1.61–2.23), but not with CDI-related complications (aOR, 0.91; 95% CI, .67–1.23) or 30-day mortality (aOR, 0.95; 95% CI, .73–1.24). Conclusions: Toxin-positive CDI is more severe, but there were no differences in adjusted CDI-related complication and mortality rates between toxin-positive and NAAT-positive-only CDI that were detected by an algorithm that utilized an initial glutamate dehydrogenase screening test. Abstract : Toxin-positive Clostridioides difficile infection (CDI) is more severe and more likely to recur as toxin positive, but there were no differences in adjusted CDI-related complication and mortality rates between toxin-positive and nucleic acid amplification test positive–only CDI.